2001
DOI: 10.1108/eum0000000005837
|View full text |Cite
|
Sign up to set email alerts
|

The role of appraisal, remuneration and training in improving staff relations in the Western Australian accommodation industry: a comparative study

Abstract: Looks at performance appraisal, remuneration and training, and the role these human resources (HR) practices have within the hotel accommodation industry in Western Australia. Owing to high turnover of staff in the hospitality and other services industries, organisations are often reluctant to invest in training on casual and part‐time employees. They are also reluctant to investigate alternative remuneration and reward strategies, despite the assistance that is provided by the Western Australian Commissioner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 14 publications
1
46
0
3
Order By: Relevance
“…Previous research (e.g. Davies, Taylor & Savery, 2001;Nolan, Conway, Farrell & Monks, 2010) support the importance of training in these three areas. Given that line managers are central to the process of workplace learning and in supporting both individual and organisational learning processes (Garavan, Morley, Gunnigle & McGuire, 2002), it is reasonable to investigate their perceptions of HRD.…”
Section: Research Design and Data Collectionmentioning
confidence: 84%
See 3 more Smart Citations
“…Previous research (e.g. Davies, Taylor & Savery, 2001;Nolan, Conway, Farrell & Monks, 2010) support the importance of training in these three areas. Given that line managers are central to the process of workplace learning and in supporting both individual and organisational learning processes (Garavan, Morley, Gunnigle & McGuire, 2002), it is reasonable to investigate their perceptions of HRD.…”
Section: Research Design and Data Collectionmentioning
confidence: 84%
“…Increased productivity is the most tangible positive outcome associated with HRD (Aksu, 2005). In their study of hotel establishments in Western Australia, Davies, Taylor and Savery (2001) found improvements in staff training had reciprocated effects on quality, productivity and reduced employee turnover. Kilic and Okumus (2005) showed that staff training and development was one of the five most important factors influencing productivity in small hotels.…”
Section: Perceived Outcomes Of Staff Training and Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Managers may be reluctant to invest in training considering that the staff might leave (Maxwell,Watson and Quail 2004;Pratten 2003;Davies, Taylor and Savery 2001;Lowry, Simon andKimberley 2002, Elnasr, A. andSobaih, E. 2011). Performing a task publicly with inappropriate skills not only impacts self-confidence but also service quality.…”
mentioning
confidence: 99%